Performance assessment of a micro solar - wind -battery scheme for residential load in Malaysia - Yong B.L.; Chia D.B.; Rajkumar R.K.; Ramachandaramurthy V.K. (2023)
Environmental concern over the use of conventional sources has reached an alarming stage, thus alternatives sources is imminent. Renewable sources such as wind and solar has gain popularity and demand over the last decade. These sources suffer from certain deficiencies when used alone. Power produced from these sources depends very much on the weather condition. Thus, combination of these sources had shown excellent potential as complementary option to generate power. This paper investigates the performance of micro scale solar-wind-battery scheme for a residential load in Malaysia. Real wind speed, solar radiation and temperature have been obtained from the Malaysian Meteorological Department and will be used as the parameters for this study. The outcome presented in this paper show potential and viability in using hybrid system to sustain residential load in Malaysia.